The development and psychometric evaluation of specific problem lists reflecting psychosocial distress of patients before and after solid organ transplantation - Müller, Evamaria; Härter, Martin; Higgen, Sanna; Barten, Markus J.; Eickhoff, Doreen; Grahammer, Florian; Reinsberg, Nele; Sterneck, Martina R.; Buchholz, Angela (Frontiers in Psychology, 2025)
IntroductionPsychosocial distress is common in patients before and after solid organ transplantation. Regular screening facilitates the early identification of distressed patients and the provision of appropriate professional care. However, feasible screening tools that address the specific problems of transplant patients are missing. Thus, the aim of this mixed methods study was to develop transplant-specific problem lists for patients before (transplant candidates) and after (transplant recipients) solid organ transplantation which can be used as a quick and easily applicable screening tool for psychosocial distress.MethodAn electronic database search resulted in a preliminary item list including 36 problems common in transplant candidates and 44 problems in transplant recipients. A total of N = 117 patients and N = 48 health care providers participated in a paper-pencil survey to assess the relevance and comprehensibility of the problem lists. Qualitative interviews about the clarity and completeness of problem lists were performed with N = 58 patients and N = 3 transplant nurses. Data analysis included the calculation of descriptive statistics and content analysis of interviews and survey open response fields. To test the concurrent validity of the problem list for patients, patients completed the problem list in combination with the National Comprehensive Cancer Network (NCNN) distress thermometer and a short form of the Patient Health Questionnaire (PHQ-4) as part of routine care.ResultsThe finalized list for transplant candidates includes 21 items and the list for transplant recipients 22 items, each covering four categories: problems in everyday life, social problems, worries and anxieties, physical and psychological problems. In the course of the study, sufficient data was gathered only from transplant recipients (N = 100). The number of problems endorsed by transplant recipients correlated significantly with measures of depression and distress (distress: r = 0.41, p < 0.001; PHQ-4: r = 0.63, p < 0.001; PHQ-2: r = 0.53, p < 0.001; GAD-2: r = 0.60, p < 0.001). The developed problem lists cover relevant psychosocial problems and can help to identify distress in patients before and after transplantation.DiscussionThe problem list for transplant recipients showed sufficient concurrent validity, psychometric properties of the problem list for transplant candidates should be investigated in further studies.